Selective and cell-active inhibitors of the USP1/UAF1 deubiquitinase complex reverse cisplatin resistance in non-small cell lung cancer cells - Chen, Junjun (2011)
Ubiquitin-specific proteases (USPs) have in recent years emerged as a promising therapeutic target class. We identified selective small-molecule inhibitors against a deubiquitinase complex, the human USP1/UAF1, through quantitative high throughput screening (qHTS) of a collection of bioactive molecules. The top inhibitors, pimozide and GW7647, inhibited USP1/UAF1 noncompetitively with a K(i) of 0.5 and 0.7 μM respectively, and displayed selectivity against a number of deubiquitinases, deSUMOylase and cysteine proteases. The USP1/UAF1 inhibitors act synergistically with cisplatin in inhibiting cisplatin-resistant non-small cell lung cancer (NSCLC) cell proliferation. USP1/UAF1 represents a promising target for drug intervention because of its involvement in translesion synthesis and Fanconi anemia pathway important for normal DNA damage response. Our results support USP1/UAF1 as a potential therapeutic target and provide the first example of targeting the USP/WD40 repeat protein complex for inhibitor discovery.